PUBLIC PERCEPTION OF CORRUPTION IN THE NIGERIAN POLICE FORCE AND ITS EFFECT ON CRIME CONTROL (Journal of the Management Sciences, 2025)
Corruption within the Nigerian Police Force (NPF) remains a critical barrier to effective crime control, manifesting through bribery, extortion, unlawful detention, and selective law enforcement. Such practices erode public trust and undermine the legitimacy of law enforcement institutions. This study examines public perceptions of corruption in the NPF and its effect on crime control. Employing a quantitative descriptive survey design, data were collected from 200 respondents and analyzed using SPSS with frequencies, tables, and charts. The study is grounded in Structural Functionalism, which emphasizes how institutions maintain social cohesion, stability, and order through clearly defined roles and responsibilities. Findings indicate that both actual and perceived corruption reduce the deterrent effect of policing, discourage crime reporting, encourage underreporting, and distort official crime statistics. The study concludes that systemic corruption significantly impairs crime control in Nigeria and recommends structural reforms, strengthened internal accountability, and enhanced procedural justice to restore public trust and improve policing effectiveness.
Keywords: Accountability; Corruption; Crime control; Nigeria Police; Public trust